Does regional redistribution spur growth? - Michael Koetter; Michael Wedow (Deutsche Bundesbank, 2008)
After the German reunification, interregional subsidies accounted for approximately four percent of gross fixed capital investment in the new federal states. We show that between 1992 and 2005 infrastructure and (small) business aid had a negative net impact on regional economic growth. This suggests that regional redistribution was ineffective, potentially due to a lack of spatial concentration to create growth poles.
Keywords: R11; R58; R42; 330; Regional growth; redistribution; infrastructure; investment subsidies; Gemeinschaftsaufgabe Regionale Wirtschaftsstruktur; Regionalpolitik; Subvention; Wirtschaftspolitische Wirkungsanalyse; Regionales Wachstum; Entwicklungskonvergenz; Neue Bundesländer; Alte Bundesländer; Deutschland